Las E-rúbricas y su incidencia en el sistema de evaluación de los estudiantes de la asignatura de Lengua y Literatura - MORÁN PIGUAVE, GINA DOLORES; Estrada Galarza, Consuelo; Tapia-Leon, Mariela; Rodríguez Caballero, Giselle (Revista Minerva, 2025)
The present study explores the incidence of e-rubrics in the evaluation system of the subject of Language and Literature for students of the “Gonzalo Córdova” School of Basic Education. The limitations of the traditional evaluation method are identified, characterized by a simple direct grade that does not completely evaluate the student or offer useful feedback for their academic development. Through a preliminary diagnosis that included surveys and interviews with students and teachers, problems of equity and personalization were evident in the current evaluation. E-rubrics, digital tools that allow for a more structured and specific assessment, are proposed as a solution to improve the accuracy and fairness of assessments. This study hypothesizes that the implementation of e-rubrics in Language and Literature increase the quality of the evaluation, facilitating more detailed feedback and promoting greater equity in the evaluation process. Preliminary results suggest a growing interest among teachers in adopting technologies that optimize the evaluation process and increase students’ motivation and academic performance. This article provides a foundation for future research on the integration of digital tools in educational assessment, highlighting the potential of e-rubrics to transform traditional assessment practices Keywords: E-rubric, evaluation, Language and Literature.